Biosorption of Lead (Pb) from Aqueous Solution by Immobilized Aspergillus niger: A Green Technology for Heavy Metals Removal - Avander Alexander Nuban; Anna Safitri; Ulfa Andayani (Program Pascasarjana Universitas Brawijaya, 2021)
Lead has very toxic properties and cannot be degraded in waters that leads to health problems, such as disorders of the nervous system, heart, kidneys, digestive tract, and causing memory loss. One of the environmentally friendly methods that can reduce and even eliminate Pb is the biosorption. One of the microorganisms that can be utilized in biosorption technology is Aspergillus niger. In the current study, Pb biosorption was carried out by modifying Aspergillus niger which was immobilized in the Ca-alginate matrix. This study aims to determine the optimum biosorption conditions which include pH, contact time, initial Pb concentration, and amount of adsorbent. Results showed that the optimum conditions for Pb biosorption were pH 6.0, with contact time of 4 h, Pb concentration was 80 ppm, and at adsorbent concentration of 3 g, with the percentage of Pb adsorbed was 98.40%. FTIR spectra results show that the Pb biosorption process causes shifts in certain wavenumbers, from 1296.16 cm-1 to 1307.74 cm-1 which was a characteristic of the amine amide (CN) group, and a shift in wavenumber from 1122.57 cm-1 to 1168.86 cm-1 which was from carboxyl functional group. The interaction between Pb and the adsorbent surface was suggested through a physical adsorption, and hence the adsorption process was reversible.